Strategi Pemanfaatan Media Sosial dan Influencer oleh Dinas Pariwisata Provinsi Sumatera Barat dalam Mempromosikan Pariwisata di Sumatera Barat - Irvan Wariski; Jumiati Jumiati (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This research was conducted with the aim of evaluating the use of social media and the role of influencers by the Tourism Office of West Sumatra Province in an effort to increase tourism promotion in West Sumatra. The research method applied is a case study approach in the context of qualitative research. To identify weaknesses and opportunities in the tourism promotion strategy implemented by the West Sumatra Tourism Office, as well as to evaluate potential deficiencies and threats that may arise in the future, SWOT analysis is used as a research tool. The research data was obtained through in-depth interviews with the staff of the Tourism Office as well as a number of tourism influencers involved in promoting tourism destinations in West Sumatra. The results of the study show that the Tourism Office of West Sumatra Province has implemented a strategy that focuses on utilizing social media and collaboration with influencers in an effort to promote tourism. In its implementation, the Tourism Office uses a collaborative approach with tourism influencers, where they involve them in content development, visits to tourist destinations, and promotional events. Apart from that, they also pay attention to performance measurement through data analysis from social media platforms and feedback from tourists. However, the implementation of tourism promotion faces several challenges such as intense competition in tourist destinations, lack of supervision of influencer content and travel media accounts and changes in social media algorithms.